A comparative evaluation of agronomic performance and kernel composition of normal and high sugary corn genotypes (Zea mays L.) grown for dry-grind ethanol production - Zabed, H.; Boyce, A.N.; Faruq, G.; Sahu, J.N. (Elsevier, 2016)
High sugary corn genotypes (Zea mays L.) have the potential to reduce enzyme consumption and enhance ethanol yield during dry-grind ethanol production. In the present work, four high sugary and four parent field corn genotypes (HSGs and PFCs, respectively) were studied comparatively to evaluate agronomic performance and kernel composition of the genotypes, as well as predict the effects of these traits on carbohydrate accumulation in the kernels. The corn genotypes were grown over two cropping years (2012 and 2013) under rain fed conditions, and some important agronomic traits and kernel biochemical components were determined. Both HSGs and PFCs varied in the agronomic properties, but these variations were not atypical in HSGs if compared with those of PFCs. The average grain yield ranged from 6.19 Mega gram per hectare (Mg/ha) to 9.43 Mg/ha in HSGs and 5.77 Mg/ha to 10.23 Mg/ha in PFCs. Sugar accumulation in the kernels was found to be negatively correlated with flowering time, grain filling period and physiological maturity of the genotypes. Compared with PFCs, a higher amount of total soluble sugars (TSS) and a lower quantity of starch were recorded in HSGs, which resulted a significant negative correlation between kernel starch and TSS. The agronomic performance and kernel composition of HSGs, particularly with high kernel sugars and low starch contents suggest that these corn genotypes could be promising candidates for producing cost-effective ethanol during dry-grind process.